2, 4-Dinitrotoluene (DNT) and 2, 4, 6-Trinitrotoluene (TNT) removal kinetics and degradation mechanism using zero valent iron-silica nanocomposite. Issue 4 (August 2018) - Shukla, Nivedita; Gupta, Vatsana; Rawat, Ashok Singh; Gahlot, Vikas Kumar; Shrivastava, Sarita; Rai, Pramod Kumar
Abstract: Magnetic zero valent iron – silica nanocomposite (Fe/SiO2 ) was synthesized using sol – gel technique followed by in-situ hydrogen reduction. The prepared nanocomposite was characterized by Nitrogen-Brunner–Emmett–Teller (N2 -BET) isotherm studies, X-Ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Transmission Electron Microscopy (TEM) and Vibrating Sample Magnetometer (VSM) techniques. The Fe/SiO2 nanocomposite demonstrated great adsorption potential against different explosives viz. 2, 4-Dinitrotoluene (DNT) and 2, 4, 6-Trinitrotoluene (TNT) with maximum adsorption capacity of 12.32 and 13.56 mg/g, respectively. Both Langmuir and Freundlich isotherm model fitted well with the experimental data indicating a heterogenous adsorption of these explosives by the nanocomposite. The magnetic Fe/SiO2 nanocomposite could be easily separated after adsorption process with the help of a magnet. A plausible reduction pathway of both the explosives using nanocomposite has also been discussed.